The Influence of Autogenic Relaxation on Anxiety of Nursing Students in Facing the Examination in School of Nursing, Surya Nusantara Pematangsiantar - Limbong, Martalina (Sari Mutiara Indonesia University Press, 2018)
Background: Anxiety is a condition that makes a person uncomfortable, related to feelings that are uncertain and helpless. Anxiety in nursing students is generally related to lectures, such as fear of failing the exam, lack of free time, and long hours of study. These anxieties can cause students to not be able to act properly and even cause a failure in the exam. Anxiety facing an exam is a problem that needs to be overcome. Student anxiety can be handled with relaxation techniques. Autogenic relaxation comes from oneself in the form of short words or sentences or thoughts that usually make the mind calm. This study aims to determine the effect of autogenic relaxation on the anxiety of nursing students when facing an exam. Methodology: This quantitative study used a quasi-experimental design, pretest-posttest design. The sampling technique with purposive sampling consisted of 23 respondents. Results: Category anxiety before being given intervention, 4 respondents (17%) with moderate anxiety, and 19 respondents (83%) with severe anxiety but after the intervention, there was a decrease in anxiety, namely 3 respondents with mild anxiety, 17 respondents with moderate anxiety and 3 respondents with severe anxiety. The results showed that the average level of anxiety before the intervention was 31.61 while the average level of anxiety after the intervention was 24.96. The results of the statistical test (Paired Sample T-Test) shows p-Value 0,000 (ie 0,000 < 0,005). Conclusion: There is an influence of autogenic relaxation on anxiety levels. Suggestion: Advise nursing students to practice relaxation techniques to reduce anxiety when taking an exam